Reality, spirituality, and modern man - Hawkins, David R., 1927-2012 (Hay House, Inc., 2021)
"Updated: This is the seventh book in a progressive series based on the revelations of consciousness research. It describes in detail how to discern not only truth from falsehood but also the illusion of appearance from the actual core of reality. The text explains how to differentiate perception from essence, and thereby enables the reader to resolve the ambiguities and classical riddles that have challenged mankind for centuries and baffled the best minds in history. While modern technologies have provided a plethora of new toys and conveniences, the basic problems of daily existence remain. This book provides the tools to survive and regain fundamental autonomy and inner harmony while living with the complexities of the modern world"--